USE OF GRADATION CORRECTION METHOD FOR IMPROVING THE VISUALIZATION OF COMPUTED TOMOGRAPHY RESULTS (Computer systems and information technologies, 2025)
The aim of this work is to enhance the quality of visualization of computed tomography (CT) results by improving digital image processing methods, particularly through the use of the gradation correction (GC). The research methodology involves the application of algorithms for the automatic determination of the optimal pixel brightness range in CT images, which reduces the influence of extreme brightness values and increases the contrast of diagnostically significant structures. The proposed gradation correction is applied not within the standard 0–255 range but based on the statistical distribution of brightness, with the exclusion of non-informative tail regions of the histogram. The research results indicate that the proposed approach improves the visual clarity of organ boundaries and pathological formations without loss of diagnostic information and can be integrated into automated medical image analysis systems. The scientific novelty of the work lies in the enhancement of the gradation correction method for CT image processing through the automation of brightness range selection. The practical significance of the study is in improving the efficiency of visual analysis and computer-aided diagnostics at the stages of preliminary medical image processing, contributing to higher accuracy in pathology detection and reduced evaluation time.
Keywords: computed tomography; gradation correction method; image processing; computer vision; contrast enhancement; software